How green are visitors at a green wine destination in South Africa? - Kruger, Martinette; Saayman, Melville (University of the Free State, 2013)
Policies that focus on the protection of the environment are continuously being developed to combat the devastating effects of global warming on, among others, the wine industry. This article segments and analyses wine visitors and their green behaviour at Spier, one of South Africa’s first wine farms to implement green initiatives. In 2011, a visitor survey was conducted at the wine farm, when 161 questionnaires were administered. Respondents were clustered according to their ‘green’ behaviours at home, and two clusters were identified: ‘dark green’ and ‘light green’ consumers. These clusters differ significantly in their green behaviour at home, their travel motives, their willingness to pay for green initiatives and their overall travel behaviour. Results also show that a green wine destination does indeed attract visitors who consider themselves to be green, and that the green brand is an attraction or unique motivation for consumers.

Beleid wat fokus op die bewaring van die omgewing word deurgaans ontwikkel om die negatiewe invloed van aardverwarming op, onder meer, die wynbedryf te bekamp. Die artikel segmenteer en analiseer die ‘groen’gedrag van wynbesoekers by een van Suid-Afrika se eerste wynplase wat omgewingsvriendelike inisiatiewe implementeer, naamlik Spier. ’n Besoekersopname is in 2011 onderneem waartydens 161 vraelyste geadministreer is. Respondente is volgens hul ‘groen’ gedrag gegroepeer. Twee is geïdentifiseer naamlik ‘donker groen’- en ‘lig groen’-verbruikers. Die twee segmente verskil statisties betekenisvol in terme van hul groengedrag by die huis, hul reismotivering, hul bereidwilligheid om meer te betaal vir groen inisiatiewe, asook hul algehele reisgedrag. Resultate bevestig dat ’n groen wynbestemming wel besoekers trek wat hulself as meer groen ag en dat die groen handelsmerk ’n unieke motivering vir besoekers is.
Keywords: Wine tourism; Environment; Wine industry; Consumers